Theoretical and methodological foundations of the development of pedagogical technology for the formation of the students needs-motivational-value sphere of physical culture - Starchanka, Uladzimir M.; Miatselitsa, Aliaksandr M. (Journal of the Belarusian State University. Journalism, 2019)
Presented the theoretical and methodological foundations of the development of pedagogical technology for the formation of the students needs-motivational-value sphere of physical culture. In particular, the authors attributed to the theoretical and methodological founPresented the theoretical and methodological foundations of the development of pedagogical technology for the formation of the students needs-motivational-value sphere of physical culture. In particular, the authors attributed to the theoretical and methodological foundations: the theories of activity, the concept of the structure and content of the need-motivational-value sphere of a person’s physical culture, the concept of the essence of the pedagogical process, the provisions of the theory of motivation, the provisions of the theory of management, the provisions of pedagogical metrology and the pro-dations: the theories of activity, the concept of the structure and content of the need-motivational-value sphere of a person’s physical culture, the concept of the essence of the pedagogical process, the provisions of the theory of motivation, the provisions of the theory of management, the provisions of pedagogical metrology and the provisions of pedagogical theory. The article also presents the structure and content of the target model of the need-motivational-value sphere of a person’s physical culture and reveals the control scheme of the technological process of its formation. visions of pedagogical theory. The article also presents the structure and content of the target model of the need-motivational-value sphere of a personʼs physical culture and reveals the control scheme of the technological process of its formation.